DEFINITION OF RATIONAL RECOVERY PERIODS OF ISOLATION EXCITING COILS OF TRACTION MOTOR - Kapitsa, M. I.; Lahuta, V. V. (Science and Transport Progress, 2006)
The article considers the task of determining the rational timing for renewal of the excitation spools insulation in tractive electric motors on the basis of prognosticating the reliability, stochastic methods being used as the reference point.